Hello!
First, let's write the problem.
![3\left(x-2\right)+2\left(x+1\right)=-14](https://tex.z-dn.net/?f=3%5Cleft%28x-2%5Cright%29%2B2%5Cleft%28x%2B1%5Cright%29%3D-14)
Apply the distributive property on the left side of the equation.
![=3x-6+2x+2](https://tex.z-dn.net/?f=%3D3x-6%2B2x%2B2)
Add like terms.
![=5x-4](https://tex.z-dn.net/?f=%3D5x-4)
Let's plug that in into the original equation.
![5x-4=-14](https://tex.z-dn.net/?f=5x-4%3D-14)
Add 4 to both sides.
![5x-4+4=-14+4](https://tex.z-dn.net/?f=5x-4%2B4%3D-14%2B4)
![5x=-10](https://tex.z-dn.net/?f=5x%3D-10)
Divide both sides by 5.
![\frac{5x}{5}=\frac{-10}{5}](https://tex.z-dn.net/?f=%5Cfrac%7B5x%7D%7B5%7D%3D%5Cfrac%7B-10%7D%7B5%7D)
Our final answer would be,
![x=-2](https://tex.z-dn.net/?f=x%3D-2)
You can feel free to let me know if you have any questions regarding this!
Thanks!
- TetraFish
Answer:
(4+√142)/(3) or x=(4-√142) /3
Step-by-step explanation:
(4+√142)/(3) or x=4-√142 /3
Answer:
say less
Step-by-step explanation:
Answer:
3x + 2x2 + 4 = 5
3x + 2x2 + 4 – 5 = 5 – 5
First be sure that the right side of the equation is 0. In this case, all you need to do is subtract 5 from both sides.
3x + 2x2 – 1 = 0
2x2 + 3x – 1 = 0
Simplify, and write the terms with the exponent on the variable in descending order.
2x2
+
3x
–
1
=
0
↓
↓
↓
ax2
bx
c
a = 2, b = 3, c = −1
Now that the equation is in standard form, you can read the values of a, b, and c from the coefficients and constant. Note that since the constant 1 is subtracted, c must be negative.
Answer
2x2 + 3x – 1 = 0; a = 2, b = 3, c = −1
Step-by-step explanation:
Answer:
20% i am not 100% sure. if i am wrong, i am sorry